The Relationships Between Parasympathetic Function and Pain Perception: The Role of Anxiety. Issue 8 (16th February 2016) - Nahman‐Averbuch, Hadas; Sprecher, Elliot; Jacob, Giris; Yarnitsky, David
Abstract: Background: Previous studies have identified relationships between autonomic function and pain perception. Anxiety was found to influence both autonomic and pain responses. We examined the effect of anxiety level on parasympathetic function and pain perception as well as on the relationships between these 2 systems. Methods: Thirty healthy females were divided into high‐ and low‐anxiety groups according to their trait anxiety levels. Parasympathetic function was obtained using heart rate variability, deep breathing, and Valsalva ratios. Pain perception parameters of heat pain thresholds, pain rating of supra‐thresholds stimulus, mechanical temporal summation, and conditioned pain modulation response were examined. Results: The low‐anxiety and high‐anxiety groups exhibited no significant differences in the parasympathetic function and pain perception parameters. Assessment of the associations revealed that in the high‐anxiety group, higher mean ratings of the tonic heat pain stimulus were significantly correlated with higher rMSSD ( r 2 = 0.358, P = 0.019), but this was not found for the low‐anxiety group ( P = 0.282). In addition, in the high‐anxiety group, efficient conditioned pain modulation response was correlated with higher deep breathing ratio ( r 2 = 0.363, P = 0.023); however, in the low‐anxiety group, the correlation did not reach significance ( P = 0.109). Conclusions: This study demonstrates the role of anxiety level on the relationships between parasympathetic function and pain perception. We suggest that a situation of high anxiety leads to higher norepinephrine levels that can influence both parasympathetic function and pain perception, thus explaining the significant relationships found between these 2 systems only in subjects with high anxiety.